Age Related Changes in Ultrastructure and Histoenzymic Distribution of Epididymis in Goat (Capra hircus) - Karmore, S. K.; Dalvi, R. S.; Meshram, B.; Deshmukh, S. K. (Indian Journal of Veterinary Anatomy, 2016)
Age related changes in the ultrastructural and histoenzymic status of the epididymis were studied on thirty goats of different age groups viz. kid, young and adult. The epididymal segments were lined by pseudostratified columnar ciliated epithelium. The epithelium had four main types of cells, principal cells, basal cells, intraepithelial lymphocytes and intraepithelial macrophages. Ciliated and non-ciliated types of principal cells were observed in almost all regions of ductules. The alkaline phosphatase activity was more in corpus epididymis, while acid phosphatase activity was observed moderate in caput epididymis. The ATPase activity was moderate to intense in stereocilia of all the regions of epididymis. The glucose-6-phosphatase showed moderate to intense activity in caput epididymis followed by corpus and cauda regions in almost all the groups of animals. The 5-nucletidase showed mild to moderate activity in all segments of epididymis.